INOCULATION OF Brachiaria decumbens WITH FORMERS FUNGI OF ARBUSCULAR MYCORRHIZAL NATIVE FROM HUMID ECUADORIAN TROPIC - Prieto Benavides, Oscar (2012)
A study was conducted under semi-controlled greenhouse conditions to determine the effect of arbuscular mycorrhizal fungi (AMF) native of traditional agroforestry system with Theobroma cacao L. (cocoa) national type (SAF-C) in the ecuadorian humid Tropics, on Brachiaria decumbens grass. The experiment was carried between june and december of 2009, constituted by five treatments, involving the inoculation of AMF originating from AFS-C, distributed in a completely random design (CRD) as follows: T1: Glomus spp., T2 : Scutellospora spp., T3: Glomus spp. + Scutellospora spp., T4: Acaulospora spp. + Gigaspora spp., T5: Control (sterile distilled H2O), in seedlings of B. decumbens planted in plastic pots of 1,000 cm3, containing as substrate a mixture of nutrient-poor soil + rice husk, steriles, in a 3:1 ratio. The inoculum was constituted by 30 spores of AMF per treatment. The variables analyzed were: a) number of spores of AMF by 100 g of moist soil (gms-1), b) percentage of visual mycorrhizal colonization and root hairs category, c) plant height, d) wet and dry weight of leaf and root systems, e) total root length (RL) and f) root density (RLv) at 78 and 103 days after inoculation. Plants inoculated with Glomus spp. or in combination with Scutellospora spp. showed better responses in the variables measured. The results demonstrated the efficiency and potential of HMA from SAF-C, on plants of B. decumbens.v